Optical spectroscopy and imaging in surgical management of cancer patients. Issue 3 (14th August 2022) - Wilson, Brian C.; Eu, Donovan
Abstract: Surgery is a pillar of cancer management, the general goal being complete removal of solid tumor tissue with minimal damage to normal tissue structure and function. Optical imaging and spectroscopy may contribute to this at several points in the procedural chain, including preoperative tumor localization and staging by biopsy, intra/perioperative identification and localization of tumor margins, detection of residual tumor tissue and tumor‐involved lymph nodes as well as critical normal tissue structures, and assessment of the viability of reconstructed tissues following tumor resection. The numerous optical modalities that can be implemented clinically are discussed, a few of which are already in clinical practice and many more are in clinical trials. These modalities utilize different light‐tissue interactions and technical approaches. The resulting biological information obtained, the current or potential clinical impact, limitations and potential future developments and roles are considered. This article is intended to inform the biophotonics community of the clinical needs and scientific/technical challenges and opportunities in photonics‐enabled surgical guidance and to guide potential surgical users on the potential advantages and limitations in this rapidly evolving landscape. Abstract : Surgery is a pillar of cancer management, the general goal being complete removal of solid tumor tissue with minimal damage to normal tissue structure and function. Optical imaging and spectroscopy may contribute to this at several points in the procedural chain, including pre‐operative tumor localization and staging by biopsy, intra/perioperative identification and localization of tumor margins, detection of residual tumor tissue and tumor‐involved lymph nodes as well as critical normal tissue structures. The numerous optical modalities that can be implemented clinically are discussed, a few of which are already in clinical practice and many more are in clinical trials.